The Effect of Barkley's family-oriented program on the burden of care on families of children with attention deficit-hyperactive disorder - Sharifeh Mousavi; Saeid Pahlavanzadeh; Tayebeh Mehrabi (Wolters Kluwer Medknow Publications, 2017)
Background: Attention deficit-hyperactive disorder (ADHD) is the most common behavioral disorders during childhood whose treatment is greatly dependent on families; therefore, families of such children should improve their relation with them so that they could enjoy their lives. Hence, this study was conducted to evaluate the effect of Barkley's family-oriented program on the burden of care on such families. Materials and Methods: This clinical trial was conducted among 64 family care givers for children with ADHD. By simple sampling, samples passing the inclusion criteria were selected and randomly allocated into two groups of control and intervention. The intervention group received Barkley's family education program through 9 sessions; the control group participated in 3 group sessions and expressed their problems and experiences. Data were collected and analyzed using the Zarit Burden Interview. Results: Burden of care was gradually reduced through the study in the intervention group, however, the mean score of burden of care did not have a significant reduction in the control group. Conclusions: Because Barkley's family-oriented program was able to reduce the burden of care in families of children with ADHD, it is recommended to develop similar programs and evaluate them through various studies.